Model Program Bimbingan Konseling Islam: Integrasi Terapi Kognitif Perilaku dan Pendekatan Psiko-Spiritual Al-Ghazali untuk Zat Adiktif - Hassan bin Awang Mat Hassan (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2026)
Substance addiction is increasing in Malaysia, causing physiological, psychological, social, and spiritual crises, particularly among Muslim patients who require holistic treatment. This study develops an integrated Islamic counseling model by combining principles of Cognitive Behavioral Therapy (CBT), such as cognitive restructuring and relapse prevention, with al-Ghazali’s psycho-spiritual concepts, including tazkiyat al-nafs, muhasabah, mujahadah, and istiqamah. Through conceptual analysis and a comprehensive literature review, this study proposes a model comprising five intervention phases—holistic assessment, self-awareness development, soul purification, behavioral modification, and consolidation—implemented through twelve structured sessions. The model aims to enhance sustainable recovery, reduce relapse rates, and support overall psychological and spiritual well-being among individuals experiencing substance addiction.